Avocado Consumption Enhances Human Postprandial Provitamin A Absorption and Conversion from a Novel High–β-Carotene Tomato Sauce and from Carrots. Issue 8 (4th June 2014) - Kopec, Rachel E.; Cooperstone, Jessica L.; Schweiggert, Ralf M.; Young, Gregory S.; Harrison, Earl H.; Francis, David M.; Clinton, Steven K.; Schwartz, Steven J.
Abstract: Dietary lipids have been shown to increase bioavailability of provitamin A carotenoids from a single meal, but the effects of dietary lipids on conversion to vitamin A during absorption are essentially unknown. Based on previous animal studies, we hypothesized that the consumption of provitamin A carotenoids with dietary lipid would enhance conversion to vitamin A during absorption compared with the consumption of provitamin A carotenoids alone. Two separate sets of 12 healthy men and women were recruited for 2 randomized, 2-way crossover studies. One meal was served with fresh avocado ( Persea americana Mill), cultivated variety Hass (delivering 23 g of lipid), and a second meal was served without avocado. In study 1, the source of provitamin A carotenoids was a tomato sauce made from a novel, high–β-carotene variety of tomatoes (delivering 33.7 mg of β-carotene). In study 2, the source of provitamin A carotenoids was raw carrots (delivering 27.3 mg of β-carotene and 18.7 mg of α-carotene). Postprandial blood samples were taken over 12 h, and provitamin A carotenoids and vitamin A were quantified in triglyceride-rich lipoprotein fractions to determine baseline-corrected area under the concentration-vs.-time curve. Consumption of lipid-rich avocado enhanced the absorption of β-carotene from study 1 by 2.4-fold ( P < 0.0001). In study 2, the absorption of β-carotene and α-carotene increased by 6.6- and 4.8-fold, respectively ( P < 0.0001 for both). Most notably, consumption of avocado enhanced the efficiency of conversion to vitamin A (as measured by retinyl esters) by 4.6-fold in study 1 ( P < 0.0001) and 12.6-fold in study 2 ( P = 0.0013). These observations highlight the importance of provitamin A carotenoid consumption with a lipid-rich food such as avocado for maximum absorption and conversion to vitamin A, especially in populations in which vitamin A deficiency is prevalent. This trial was registered at clinicaltrials.gov as NCT01432210.